Understanding CO2-brine-wellbore cement-rock interactions for CO2 storage - Farooqui,NM; Liu,Q; Maroto-Valer,MM; Mosleh,MH; Korre,A; Durucan,S (Elsevier, 2017)
There is a need to improve our understanding of wellbore integrity by conducting investigations into the flow, geomechanical and geochemical properties of cement and reservoir rocks under conditions representative of subsurface temperatures and pressures at the wellbore. A series of composite cement-host rock core samples were prepared and subjected to baseline flow and mechanical properties testing to determine porosity, permeability, strength and elastic properties. The hydrothermal experiments conducted have shown that variations in the solution profiles of Ca, Mg, and Fe were due to the dissolution of CO 2 for all sets of samples. The dissolution of muscovite and montmorillonite from the composite core samples resulted in increasing concentrations of Na, K and S.